WHY ASUS ROG? ANALYSIS THE ANTECEDENT FACTOR BEHIND CUSTOMER LOYALTY - Sari, Titik Yulita; Mantara, Angga Yuni (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.12.TAHUN.2024DO - 10.24843/EEB.2024.v13.i12.p04, 2024)
Customer Loyalty is a valuable asset that must be built by brand owners, so that consumers continue to make repeat purchases of the products they have. This study aims to determine the effect of Purchase Intention and Customer Perceived Quality in mediating Brand Personality with Customer Loyalty on ASUS ROG Laptop users. Data collection in this study used a questionnaire given to 100 respondents on the Indonesian Laptop Gaming Community Facebook group. This study uses a quantitative approach with explanatory analysis and SMARTPLS 4.0. The findings show that Purchase Intention and Customer Perceived Quality significantly mediate the relationship between Brand Personality and Customer Loyalty, with a low level of mediation for the Purchase Intention variable and a high level of mediation for the Customer Perceived Quality variable. The results of the study highlight the important role of Purchase Intention and Customer Perceived Quality as a form of increasing Customer Loyalty on the ASUS ROG Laptop Brand.